Quality in turning of Inconel X-750 superalloy - AY, MUSTAFA (ICE PUBLISHING, 2020)
This study has been conducted to analyse the effects of turning the Inconel X-750 superalloy, which is a member of a nickel-based superalloy family that is frequently preferred in the aerospace and nuclear energy industries in particular, under minimum quantity lubrication (MQL), cryogenic liquid nitrogen (LN2 ) and carbon dioxide gas (CO2) cooling/lubrication conditions, with different cutting speeds (V-c = 65, 95, 125 and 155 m/min) and constant feed rate (f=0.1 mm/revolution) and cutting depth (a =0.5 mm) parameters, on the processability of Inconel X-750, hence on the surface integrity. In this context, the results obtained from the tests have been comparatively examined through surface roughness, tool wear and chip formation. Comparison results show that the cryogenic carbon dioxide method has generally provided the best surface roughness and tool wear values. The MQL method has provided the best chip formation.
Keywords: manufacturing; material processing; surface; SURFACE INTEGRITY ANALYSIS; MACHINING PARAMETERS; HIGH-PERFORMANCE; CUTTING FLUID; COOLANT; TOOL; ROUGHNESS; DRY; STRATEGIES; ALLOY